Odpowiedzi

2010-03-23T18:27:13+01:00
A x=1
b x=1
c x-2
d x=2
e x=-7
f x= -2
2010-03-23T18:27:22+01:00
A)2(x-1/2)-x +3=3
2x-1-x+3=32x-x=3-3+1
x=1

b)0=3-(2x+1)
0= -6x-3
0+3= -6x
3= -6x /÷(-6)
-1/2=x

1 2 1
2010-03-23T18:37:31+01:00
A) 2 * x - 2 * 1/2 - x +3=3
2x - 1 - x + 3=3
2x - x= 1 - 3 +3
x=1

b) 0= 3 (2x -1)
0= 3 * 2x - 3 * 1
0= 6x - 3
0 + 3= 6x
6x=3/:6
x=1/2

c) 0= 1x- 7x
0= -6x
-6x=0/:6
x=0

d) -1 1/2x + 1.5 x=3
x=3

e)3(1 - x ) - ( 1 - 2x ) = 9
3 * 1 - 3 * x - 1x=9
3 - 3x + 1x=9
3x + 1x=9 - 3
3x= 6//3
x=2

f) 0,5(2 - 4x ) = 3 - x
0.5 * 2 - 0.5 * 4x= 3 - x
1 - 2x=3 - x
-2x + x= -1 + 3
x=2